[OP.7D.08] SEVERE RESISTANT HYPERTENSION EXHIBITS THE GREATEST CARDIOVASCULAR RISK AMONG TREATED UNCONTROLLED HYPERTENSIVES: A 4-YEAR FOLLOW-UP STUDY. (September 2016) - Kasiakogias, A.; Tsioufis, C.; Kordalis, A.; Dimitriadis, K.; Andrikou, E.; Andrikou, I.; Flessas, D.; Chatzis, D.; Aragiannis, D.; Valenti, P.; Tousoulis, D.
Abstract : Objective: Data regarding the prognosis of resistant hypertension (RHT) with respect to its severity is limited. We investigated the cardiovascular risk of severe RHT among patients with treated uncontrolled hypertension. Design and method: In a prospective observational study, 1700 hypertensive patients (aged 57±12 years, 50% males) with office blood pressure (BP) >or = 140 and/or 90mmHg despite antihypertensive treatment, were followed for a mean period of 3.6±1.8 years. At baseline, clinical data were collected and patients underwent echocardiographic measurements, routine blood testing and additional workup for exclusion of secondary causes of RHT. Three groups were identified depending on presence of RHT (office-based uncontrolled hypertension under at least 3 drugs including a diuretic) and levels of office systolic BP: 1, 187 patients (70%) without RHT, 313 (18%) with not-severe RHT (systolic BP < 160mmHg) and 200 (12%) with severe RHT (systolic BP >or = 160mmHg). Endpoint of interest was cardiovascular morbidity set as the composite of coronary heart disease and stroke. Results: During follow-up, 58 events were recorded (9.5 cases per 1, 000 person-years). Incidence rates of cardiovascular events were 7.1 cases per 1, 000 person-years in the group without RHT, 12.4 cases per 1, 000 person-years in the group with not-severe RHT and 18 cases per 1, 000 person-years in the severe RHT group. Unadjusted analysis showed that compared to uncontrolled patients without RHT, patients with not-severe RHT exhibited a similar risk but patients with severe RHT had a significantly higher risk by 2.5 times (CI: 1.28–4.73, p = 0.007) for the composite cardiovascular outcome. Multivariate cox regression revealed that even after adjusting for a series of established risk factors, severe RHT remained as an independent predictor of the cardiovascular outcome, (OR:2.57, CI:1.27–5.19, p = 0.008). Conclusions: Among treated yet uncontrolled hypertensive patients, severe RHT exhibits a significantly higher cardiovascular risk indicating the need for prompt management.